PURIFICATION AND CHARACTERIZATION OF POLY-HYDROXYBUTYRATE (PHB) IN CUPRIAVIDUS NECATOR - Sergio Leon De Rooy; Endang Tri Wahyuni; Wiratni Wiratni; Siti Syamsiah; Jamil Ismail (Indonesian Journal of Chemistry, 2007)
Purification and characterization of biodegradable plastic namely Polyhydroxybutyrate (PHB) in Cupriavidus necator have been carried out. C. necator was grown on a Ramsay medium with fixed substrate conditions and optimized for time. Stepwise purification of PHB was carried out, by using hydrogen peroxide and chloroform. The effect of temperature, time, and hydrogen peroxide concentration on the purification were also evaluated. The extracted PHB was studied with XRD, FTIR and 1H-NMR and 13C-NMR to determine its structure and purity. Yield and crystallinity were also studied with HPLC and XRD, respectively. The results of the research showed that higher concentrations of hydrogen peroxide gave better yields, whereas higher temperatures and longer lysis times led to different results. Higher crystallinity was observed when purification temperatures were elevated, but higher hydrogen peroxide concentration and longer extraction time gave varying crystallinity. The highest yield ca 66.10 % DCW was reached by purification using H2O2 20 %, at 100 oC for 2 h. The results of   TGA analysis indicated that the purity of the PHB obtained was about 75 % and by using DSC, it was found that the PHB showed good thermal properties.